'Which treatment do you believe you received?' A randomised blinding feasibility trial of spinal manual therapy - Javier Muñoz Laguna; Astrid Kurmann; Léonie Hofstetter; Emanuela Nyantakyi; Julia Braun; Lauren Clack; Heejung Bang; Mazda Farshad; Nadine E. Foster; Milo A. Puhan; Cesar A. Hincapié; the SALuBRITY Blinding Clinician Group (Chiropractic & Manual Therapies)
Abstract Background Blinding is essential for mitigating biases in trials of low back pain (LBP). Our main objectives were to assess the feasibility of blinding: (1) participants randomly allocated to active or placebo spinal manual therapy (SMT), and (2) outcome assessors. We also explored blinding by levels of SMT lifetime experience and recent LBP, and factors contributing to beliefs about the assigned intervention. Methods A two-parallel-arm, single-centre, placebo-controlled, blinding feasibility trial. Adults were randomised to active SMT (n = 40) or placebo SMT (n = 41). Participants attended two study visits for their assigned intervention, on average seven days apart. The primary outcome was participant blinding (beliefs about assigned intervention) using the Bang blinding index (BI) at two study visits. The Bang BI is arm-specific, chance-corrected, and ranges from − 1 (all incorrect beliefs) to 1 (all correct beliefs), with 0 indicating equal proportions of correct and incorrect beliefs. Secondary outcomes included factors contributing to beliefs about the assigned intervention. Results Of 85 adults screened, 81 participants were randomised (41 [51%] with SMT lifetime experience; 29 [39%] with recent LBP), and 80 (99%) completed follow-up. At study visit 1, 50% of participants in the active SMT arm (Bang BI: 0.50 [95% confidence interval (CI), 0.26 to 0.74]) and 37% in the placebo SMT arm (0.37 [95% CI, 0.10 to 0.63]) had a correct belief about their assigned intervention, beyond chance. At study visit 2, BIs were 0.36 (0.08 to 0.64) and 0.29 (0.01 to 0.57) for participants in the active and placebo SMT arms, respectively. BIs among outcome assessors suggested adequate blinding at both study visits (active SMT: 0.08 [− 0.05 to 0.20] and 0.03 [− 0.11 to 0.16]; placebo SMT: − 0.12 [− 0.24 to 0.00] and − 0.07 [− 0.21 to 0.07]). BIs varied by participant levels of SMT lifetime experience and recent LBP. Participants and outcome assessors described different factors contributing to their beliefs. Conclusions Adequate blinding of participants assigned to active SMT may not be feasible with the intervention protocol studied, whereas blinding of participants in the placebo SMT arm may be feasible. Blinding of outcome assessors seemed adequate. Further methodological work on blinding of SMT is needed. Trial registration number NCT05778396.